Real‐World Data on Lymphoma in Adolescents and Young Adults (AYA)—Report From the Lymphoma and Related Diseases Registry (LaRDR) - Evangeline Y. Wong; Cameron Wellard; Jun Yen Ng; Eliza Chung; Zoe K. McQuilten; Stephen Opat; Erica M. Wood; Dipti Talaulikar (eJHaem)
ABSTRACT Introduction Lymphoma is a common malignancy among adolescents and young adults (AYAs) which is generally defined as 15–39 years. Relative to other age groups, lymphoma in AYAs remains understudied with heterogeneous treatment options. Methods We performed a retrospective review of patients aged 18–60 years in the Australasian Lymphoma and Related Diseases Registry (LaRDR) with new diagnoses of the common subtypes of lymphoma in AYAs between January 2016 and April 2023. The subtypes are classic Hodgkin lymphoma (cHL), diffuse large B‐cell lymphoma (DLBCL), primary mediastinal B‐cell lymphoma (PMBCL) and Burkitt lymphoma (BL). Patient demographics, disease characteristics, treatment and outcome data were collected, and comparisons were made between AYAs (18–39 years) and older adults (OAs) (aged 40–60). Results AYAs had higher rates of cHL and PMBCL whereas OAs presented more frequently with DLBCL. AYAs with cHL and PMBCL had higher rates of early‐stage and low‐risk disease than OAs. In contrast, both AYAs and OAs were more likely to present with advanced‐stage DLBCL and BL. AYAs with cHL were more likely to be treated with BEACOPP as compared to OAs who were more commonly treated with ABVD. There was no significant difference in treatment regimens for DLBCL, PMBCL or BL between AYAs and OAs. AYAs with cHL had better overall survival (OS) compared to OAs; specifically, cHL AYAs had better OS and DLBCL AYAs had better progression‐free survival (PFS) and OS compared to OAs. Conclusion The study provides valuable data on patient and disease characteristics, treatments used and outcomes in AYA compared to OA aged 40–60 years. Registry data such as from LaRDR can help improve treatment standardisation and AYA patient outcomes. Trial Registration The authors have confirmed clinical trial registration is not needed for this submission